2010
DOI: 10.1038/sj.bjc.6605838
|View full text |Cite|
|
Sign up to set email alerts
|

Pooled analysis of recent studies on magnetic fields and childhood leukaemia

Abstract: Background:Previous pooled analyses have reported an association between magnetic fields and childhood leukaemia. We present a pooled analysis based on primary data from studies on residential magnetic fields and childhood leukaemia published after 2000.Methods:Seven studies with a total of 10 865 cases and 12 853 controls were included. The main analysis focused on 24-h magnetic field measurements or calculated fields in residences.Results:In the combined results, risk increased with increase in exposure, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
154
3
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 207 publications
(170 citation statements)
references
References 19 publications
9
154
3
4
Order By: Relevance
“…The obtained results deny the hypotheses that nighttime measures are more suitable. [22], presented a pooled analysis on primary data from studies on residential magnetic fields and childhood leukemia published after 2000. The main analysis focused on 24-hrs magnetic field measurements, and the results were presenting relation between magnetic fields and childhood leukemia.…”
Section: Relation Between Elf-emf and Childhood Leukemiamentioning
confidence: 99%
“…The obtained results deny the hypotheses that nighttime measures are more suitable. [22], presented a pooled analysis on primary data from studies on residential magnetic fields and childhood leukemia published after 2000. The main analysis focused on 24-hrs magnetic field measurements, and the results were presenting relation between magnetic fields and childhood leukemia.…”
Section: Relation Between Elf-emf and Childhood Leukemiamentioning
confidence: 99%
“…Ainsi dans l'analyse « poolée » de Kheifets et al (2010), les expositions des études prises en compte étaient différentes sans critère logique les reliant entre elles. Certes elles concernaient l'exposition dans la résidence de l'enfant, mais trois appréciaient le CM mesuré dans la chambre de l'enfant pendant 24 h (Schüz et al, 2001 ;Wünsch-Filho et al, 2011) ou une semaine (Kabuto et al, 2006), trois le CM calculé, en tenant compte de l'historique de charge de la ligne et d'autres caractéristiques de la ligne (Bianchi et al, 2000 ;Kroll et al, 2010 ;Malagoli et al, 2010) tandis que la dernière se basait sur la distance entre la résidence et la ligne la plus proche (Lowenthal et al, 2007).…”
Section: La Question Des Leucémies De L'enfantunclassified
“…Ahlbom's "pooled" study (Ahlbom et al, 2000) is the one that has been taken into account in the expertise of the International Agency for Research on Cancer. Kheifets's "pooled" study (Kheifets et al, 2010) is the latest : it takes into account epidemiological studies published between 2000 and 2010.…”
Section: La Question Des Leucémies De L'enfantmentioning
confidence: 99%
“…Since then, a large number of epidemiological studies have been published, investigating the suggested association between extremely low frequency (ELF) EMF and childhood leukaemia (see Kheifets & Shimkhada (2005) for an extensive review). In three pooled analyses (Ahlbom et al 2000, Greenland et al 2000, Kheifets et al, 2010) on previously published case-control studies, an increased relative risk at higher magnetic field strength was found. A biophysical mechanism that could support and verify this suggested association has not been found in ongoing scientific research, although several mechanisms have been hypothesised (see Gee, 2009).…”
mentioning
confidence: 99%